Conserving Kurdish Poetry and Poets as of the National Culture in ( Dengi geti taze) - ئەمین عبداللە, موحەمەد; عبداللە کریم, نیگار (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The traditional significances of (Dengî gêtî taze) in journalism are demonstrated as a national culture was a significant medium. Over time its importance and advantage have increased, so as to aware the society about contemporary happenings at its era. (D. G. T) has assisted the poets to publish their products, in addition to publish the classical poetry. in the literal and traditional domains of (language, poetry, essay….). Each of these branches handles many more traditional domains. These domains have been serving Kurdish tradition. The importance of (poetry) -which refers to Kurdish national symbols-, has been shown by the writers. However, poetry. Poetry has started to affect each Kurdish individual psych from classical era and on. The component -society, culture…Of the poems has squirted from poets' hearts and emotions. Classical poetry has always been repeated orally by Kurdish individuals. It has enriched Kurdish meetings…... That was these poets who took initiative to the contemporary poetry.